Strong winds at Allahabad and their forewarnings (MAUSAM, 1952)
A study of the strong surface winds that occur at Allahabad (Bamrauli Aerodrome) has been made, Records of the wind velocity of 20 mph or more during the period 1941-45 have been analysed. The caution and a strong winds have been classified Into three groups, (I) Strong gusty winds, as experienced in the summer or those in monsoon, not connected with monsoon depressions,  (2) strong winds, accompanying the depressions and {3) squally winds, associated with dust and thunderstorms. General cha~teristic8 of the different types of the strong winds and the associated synoptic situations are discussed. Some local indications at the station and at a few neighbouring stations which have been found useful for the issue of short-time warnings for the squally or convergence winds that are associated with the severe duststorms and thunderstorms of the summer months are also discussed.